Experimental study on acoustic emission characteristics of jointed rock mass by double disc cutter - Lin, Qi-bin; Cao, Ping; Li, Kai-hui; Cao, Ri-hong; Zhou, Ke-ping; Deng, Hong-wei (Journal of Central South University, 2018)
The characteristics of joints are crucial factors which influence the penetration efficiency of tunnel boring machine (TBM). Based on the theoretical study, numerical simulation and experimental research, many researchers have studied the interaction between TBM disc cutters and jointed rock mass. However, in most of these works, the effect of joint on rock fragmentation by double disc cutter has been scarcely investigated. Thus, the effects of joint orientation and joint space on rock fragmentation by double disc cutter are highlighted in this study. During the test, jointed concrete specimens are adopted to simulate jointed rock mass. Improved RYL-600 rock shear rheological instrument was employed during the indentation process under disc cutters, and acoustic emission location system was used to analyze the rock damage and physical deterioration. The results show that there are four failure modes and three modes of crack initiation and propagation in jointed rock mass. It is concluded that the existing joint planes have obviously restrained the crack initiation and propagation during the rock fragmentation process. The results also indicate that samples are damaged most seriously when joint orientation equals 60°, which is proved to be the optimum joint orientation in TBM penetration.